Expressão membrano-citoplasmática do EGFR e estado mutacional do RAS expandido em carcinomas colorretais: estudo de acurácia - Pinto, Thiago David Alves (2017)
Epidermal growth factor receptor inhibitors represent a treatment option with proven efficacy for patients with metastatic colorectal carcinoma. However, patients with activating mutations in KRAS and NRAS have no response. Currently, wild KRAS and NRAS are prerequisite for this therapy. Furthermore, mutation tests are expensive and not easily accessible. EGFR expression by immunohistochemistry predicting the expanded RAS mutation (KRAS and NRAS), may allow the treatment to be instituted through a less costly and more accessible diagnostic method. The objective of this study is to test the correlation between EGFR cytoplasmic-membrane expression and the mutational status of the expanded RAS in colorectal carcinomas. An accuracy analysis was performed on 139 patients with colorectal carcinoma selected from the archives of the Instituto Goiano de Oncologia e Hematologia. The correlation between clinical-pathological data, the mutational state of the expanded RAS and the pattern of EGFR cytoplasmic-membrane expression were investigated. The expanded RAS mutation was detected in 78 (56.1%) cases. EGFR expression was stratified into 23 (16.5%) "Positives", 49 (35.2%) "Negatives" and 67 (48.2%) "Uncertain" cases. There was no significant association between age (p = 0.541 and 0.652), sex (p = 0.388 and 0.540), location (p = 0.393 and 0.098), histological type (p = 0.199 and 0.697), histological grade (p = 0.900 and 0.182) and stage (p = 0.533 and 0.053). The expression of EGFR stratified in "Positives", "Negatives" and "Uncertain" compared to the mutational status of the expanded RAS showed a strong association between the groups (p <0.001). Of the 23 "Positive" cases, 21 (91.3%) showed wild RAS gene. Of the 49 "Negative" cases, 41 (83.7%) presented mutation in the expanded RAS panel. Therefore, our study is pioneer in revealing that the EGFR cytoplasmic-membrane analysis, stratified in "Positives," "Negatives" and "Uncertain", predicts the mutational state of RAS in 51.7% of cases (p <0.001), with 86.1% accuracy. However further studies are needed to determine why nearly half of the cases are still doubtful. More complete analyzes contemplating the amplification of EGFR and mutations in other EGFR / MAPK cascade genes such as BRAF and PIK3CA, could enable a better stratification of the population.